HIF prolyl hydroxylase inhibition prior to transient focal cerebral ischaemia is neuroprotective in mice. - Chen, R; Ogunshola, O; Yeoh, K; Jani, A; Papadakis, M; Nagel, S; Schofield, C; Buchan, A (2014)
This study investigated the effects of 2-(1-chloro-4-hydroxyisoquinoline-3-carboxamido) acetic acid (IOX3), a selective small molecule inhibitor of hypoxia-inducible factor (HIF) prolyl hydroxylases, on mouse brains subject to transient focal cerebral ischaemia. Male, 8- to 12-week-old C57/B6 mice were subjected to 45 min of middle cerebral artery occlusion (MCAO) either immediately or 24 h after receiving IOX3. Mice receiving IOX3 at 20 mg/kg 24 h prior to the MCAO had better neuroscores and smaller blood-brain barrier (BBB) disruption and infarct volumes than mice receiving the vehicle, whereas those having IOX3 at 60 mg/kg showed no significant changes. IOX3 treatment immediately before MCAO was not neuroprotective. IOX3 up-regulated HIF-1α, and increased EPO expression in mouse brains. In an in vitro BBB model (RBE4 cell line), IOX3 up-regulated HIF-1α and delocalized ZO-1. Pre-treating IOX3 on RBE4 cells 24 h before oxygen-glucose deprivation had a protective effect on endothelial barrier preservation with ZO-1 being better localized, while immediate IOX3 treatment did not. Our study suggests that HIF stabilization with IOX3 before cerebral ischaemia is neuroprotective partially because of BBB protection, while immediate application could be detrimental. These results provide information for studies aimed at the therapeutic activation of HIF pathway for neurovascular protection from cerebral ischaemia. We show that IOX3, a selective small molecule (280.66 Da) HIF prolyl hydroxylase inhibitor, could up-regulate HIF-1α and increase erythropoietin expression in mice. We further demonstrate that HIF stabilization with IOX3 before cerebral ischaemia is neuroprotective partially because of blood-brain barrier (BBB) protection, while immediate application is detrimental both in vivo and in vitro. These findings provide new insights into the role of HIF stabilization in ischaemic stroke.